2019
DOI: 10.1021/acschembio.9b00634
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Rational Approach to Design Split G-Quadruplex Probes

Abstract: Hybridization probes have become an indispensable tool for nucleic acid analysis. Systematic efforts in probe optimization resulted in their improved binding affinity, turn-on ratios, and ability to discriminate single nucleotide substitutions (SNSs). The use of split (or multicomponent) probes is a promising strategy to improve probe selectivity and enable an analysis of folded analytes. Here, we developed criteria for the rational design of a split G-quadruplex (G4) peroxidase-like deoxyribozyme (sPDz) probe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…Despite the presence of nonspecific amplification products, the negative control samples did not produce appreciable color change (Figure 3A, sample 1). Indeed, we and others have earlier demonstrated that the biPxD probes have exceptional selectivity enabling differentiation of single nucleotide substitutions (SNP) in nucleic acids even at room temperature [20,22,23,36] . Therefore, the approach described here can potentially enable detection of point mutations for determination of drug resistance and genotyping bacteria, which will be demonstrated in the follow up studies.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…Despite the presence of nonspecific amplification products, the negative control samples did not produce appreciable color change (Figure 3A, sample 1). Indeed, we and others have earlier demonstrated that the biPxD probes have exceptional selectivity enabling differentiation of single nucleotide substitutions (SNP) in nucleic acids even at room temperature [20,22,23,36] . Therefore, the approach described here can potentially enable detection of point mutations for determination of drug resistance and genotyping bacteria, which will be demonstrated in the follow up studies.…”
Section: Resultsmentioning
confidence: 82%
“…Extra nucleotides non‐complementary to the analyte were added to both strand m and f (shown in low cases in Figure 2A). These nucleotides were required to fold the stands in stem‐loop structures (Figure 2C) and reduce their associations in G‐4 in the absence of analytes [36] . Probes with strands lacking intramolecular folding produced high background color change in the absence of analytes (data not shown).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…S3). The discriminatory ability of the split probes can be improved via one of the two approaches (Connelly et al, 2019). In the first approach, the target-binding fragment of strand S was shortened to form strand S2 (Fig.…”
Section: Selectivitymentioning
confidence: 99%